2020
DOI: 10.3390/ijerph17051552
|View full text |Cite
|
Sign up to set email alerts
|

Disparity in Risk Factor Severity for Early Childhood Blood Lead among Predominantly African-American Black Children: The 1999 to 2010 US NHANES

Abstract: There is no safe detectable level of lead (Pb) in the blood of young children. In the United States, predominantly African-American Black children are exposed to more Pb and present with the highest mean blood lead levels (BLLs). However, racial disparity has not been fully examined within risk factors for early childhood Pb exposure. Therefore, we conducted secondary analysis of blood Pb determinations for 2841 US children at ages 1-5 years with citizenship examined by the cross-sectional 1999 to 2010 Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 111 publications
1
40
0
Order By: Relevance
“…It is caused by children's behavior to bite and swallow anything that makes them easier to expose by pollutants. These results are also supported by a literature review conducted on African-American Black children from 1999 to 2010, which states that children have a higher risk of Pb poisoning in their growth periods (12). Inhaled Pb in humans will be stored in the lungs by 35-40%, and 95% will enter the bloodstream.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…It is caused by children's behavior to bite and swallow anything that makes them easier to expose by pollutants. These results are also supported by a literature review conducted on African-American Black children from 1999 to 2010, which states that children have a higher risk of Pb poisoning in their growth periods (12). Inhaled Pb in humans will be stored in the lungs by 35-40%, and 95% will enter the bloodstream.…”
Section: Discussionsupporting
confidence: 56%
“…Pb exposure in children and adulthood is very important to analyze because it will affect their intelligence, behavior, memory, and brain volume in the longterm exposure (12). While, a short period of Pb exposure might be impacted to the prefrontal cerebral cortex, hippocampus, and cerebellum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent events indicate that a significant number of municipalities suffer from Pb 2+ contamination in drinking water in homes and schools throughout the United States (Hanna-Attisha et al, 2016). Childhood Pb 2+ intoxication is most likely to occur in low-income, inner city communities where there is a higher number of Pb 2+ contaminated homes and decaying infrastructure with a disproportionate burden in disadvantage African American and Hispanic communities (Cassidy-Bushrow et al, 2017;Rothweiler et al, 2007;White et al, 2016;Yeter et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the risk of lead exposure is not evenly distributed across the US population, with greater risks for communities of color and residents in urban and low-income areas where older, lead-contaminated homes are located. Studies reported consistent and significant racial disparity in lead exposure across the nation with higher blood lead levels for non-Hispanic Black children compared to non-Hispanic whites even after correcting for other housing or socioeconomic risk factors [ 14 , 18 , 19 , 20 , 21 ]. Therefore, additional strategies need to be deployed to remedy these racial disparities in lead exposure.…”
Section: Introductionmentioning
confidence: 99%